Comparison of the efficacy of chemomechanical caries removal (Carisolv™) with that of conventional excavation in reducing the cariogenic flora - B. AZRAK, A. CALLAWAY, A. GRUNDHEBER, E. STENDER, & B. WILLERSHAUSEN (Paediatric Dentistry, 2004)
The usage of minimally invasive procedures and attention to patient comfort are of great importance, especially for dental treatment in small children.